Using the Intramolecular Contribution to the Second Moment of NMR Line Shape to Detect Site Symmetry Breakdown in Molecular Crystals. (20th December 2015) - Bashirov, Ferid; Gaisin, Nail
Abstract : A new approach to simulating the intramolecular contribution to the anisotropic second moment of NMR spectral lines broadened by magnetic dipole-dipole interaction of nuclei is suggested. The extended angular jump model is used by approximating the local hindered molecular motion (HMM). The theoretical result allow describing the site symmetry distortion by new experimental parameters q α, the dynamic weights of irreducible representations of the HMM crystallographic point symmetry group. The application of the theory to describing the intraionic second moment of the proton NMR spectral line in monocrystalline ammonium chloride proves the tetragonal distorted tetrahedral site symmetry of ammonium ions.